2018
DOI: 10.1101/365486
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining the genetic control of human blood plasma N-glycome using genome-wide association study

Abstract: 45Glycosylation is a common post-translational modification of proteins. It is known, that glycans 46 are directly involved in the pathophysiology of every major disease. Defining genetic factors 47 altering glycosylation may provide a basis for novel approaches to diagnostic and pharmaceutical 48 applications. Here, we report a genome-wide association study of the human blood plasma N-49 glycome composition in up to 3811 people. We discovered and replicated twelve loci. This 50 allowed us to demonstrate a cle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 68 publications
1
35
0
Order By: Relevance
“…Further, given the effect of alternative N-glycosylation at the Asn297 site in the Fc domain of IgG on antibody effector function ( 37 ) and the initial observations of hypogalactosylation associated with ZIP8 391-Thr ( 19 , 21 ), we hypothesized that there would be an association between ZIP8 391-Thr and N-glycosylation of IgG. To study associations between ZIP8 391-Thr and the N-glycome, we used GWAS of human blood plasma ( n = 2763) ( 38 ) and IgG N-glycome ( n = 8080) ( 39 ), where N-glycome profiles were analyzed using ultra-high-performance liquid chromatography (UHPLC). The frequency of ZIP8 391-Thr was 8% and 8.3%, respectively; notably, ZIP8 391-Thr (rs13107325) was not included in the initial analyses, as it was not included on the original genotyping arrays.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, given the effect of alternative N-glycosylation at the Asn297 site in the Fc domain of IgG on antibody effector function ( 37 ) and the initial observations of hypogalactosylation associated with ZIP8 391-Thr ( 19 , 21 ), we hypothesized that there would be an association between ZIP8 391-Thr and N-glycosylation of IgG. To study associations between ZIP8 391-Thr and the N-glycome, we used GWAS of human blood plasma ( n = 2763) ( 38 ) and IgG N-glycome ( n = 8080) ( 39 ), where N-glycome profiles were analyzed using ultra-high-performance liquid chromatography (UHPLC). The frequency of ZIP8 391-Thr was 8% and 8.3%, respectively; notably, ZIP8 391-Thr (rs13107325) was not included in the initial analyses, as it was not included on the original genotyping arrays.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the association between ZIP8 391-Thr and human N-glycome in human population-based samples, we used the results of recently published GWAS of human blood plasma N-glycome ( n = 2763) ( http://doi.org/10.5281/zenodo.1298406 ) ( 38 ) and IgG N-glycome ( n = 8080) ( https://datashare.is.ed.ac.uk/handle/10283/3238 ) ( 39 ), where N-glycome profiles were analyzed using UHPLC. We performed a single-SNP glycome-wide association analysis among 113 total plasma N-glycome traits and 77 IgG N-glycome traits using publicly available GWAS summary statistics.…”
Section: Methodsmentioning
confidence: 99%
“…To further validate our findings, we analyzed all significantly associated SNPs in a cohort where glycans were measured with liquid chromatography coupled to electrospray mass spectrometry (LCMS; N = 1842). From the 27 genome-wide significant SNPs, 17 were associated with at least one of the LCMS-measured IgG glycopeptide levels at Bonferroni-corrected P ≤ 3.7 × 10 −5 . Of these 17, 14 loci were also replicated in the UPLC replication study (table S2).…”
Section: Discovery and Replication Meta-analysesmentioning
confidence: 99%
“…None of the randomly selected SNPs exhibited such a strong correlation with these two loci in the permutation analysis ( Table 2 and table S6). Recent work by Sharapov et al (17) on genetics of the total plasma proteome N-glycosylation, of which IgG is a major part, suggested that the likely candidate gene is DERL3. DERL3 encodes a protein involved in endoplasmic reticulum-associated degradation for misfolded luminal glycoproteins.…”
Section: Functional Network Of Loci Associated With Igg N-glycosylationmentioning
confidence: 99%
“…Previous work has investigated the similarity across glycans using glycan motifs, such as, glycan fingerprinting to describe glycan diversity in databases 17 , align glycan structures 18 , identify glycan epitopes in glycoprofiles 19 , deconvolve LC-MS data to clarify glycan abundance 20 , or compare glycans in glycoprofiles leveraging simple structures 21 . These tools use information on glycan composition or epitopes; however, further accounting for shared biosynthetic steps across glycans could provide complete biosynthetic context to all glycan epitopes.…”
Section: Introductionmentioning
confidence: 99%